Heat treatment of peach fruit: Modifications in the extracellular compartment and identification of novel extracellular proteins - Bustamante, Claudia Anabel; Budde, Claudio Olaf; Borsani, Julia; Lombardo, Verónica Andrea; Lauxmann, Martin Alexander; Andreo, Carlos Santiago; Lara, María Valeria; Drincovich, María Fabiana (Elsevier, 2024)
Ripening of peach (Prunus persica L. Batsch) fruit is accompanied by dramatic cell wall changes that lead to softening. Post-harvest heat treatment is effective in delaying softening and preventing some chilling injury symptoms that this fruit exhibits after storage at low temperatures. In the present work, the levels of twelve transcripts encoding proteins involved in cell wall metabolism, as well as the differential extracellular proteome, were examined after a post-harvest heat treatment (HT; 39 °C for 3 days) of “Dixiland” peach fruit. A typical softening behaviour, in correlation with an increase in 1-aminocyclopropane-1-carboxylic acid oxidase-1 (PpACO1), was observed for peach maintained at 20 °C for 3 days (R3). Six transcripts encoding proteins involved in cell wall metabolism significantly increased in R3 with respect to peach at harvest, while six showed no modification or even decreased. In contrast, after HT, fruit maintained their firmness, exhibiting low PpACO1 level and significant lower levels of the twelve cell wall-modifying genes than in R3. Differential proteomic analysis of apoplastic proteins during softening and after HT revealed a significant decrease of DUF642 proteins after HT; as well as an increase of glyceraldehyde-3-phosphate dehydrogenase (GAPC) after softening. The presence of GAPC in the peach extracellular matrix was further confirmed by in situ immunolocalization and transient expression in tomato fruit. Though further studies are required to establish the function of DUF642 and GAPC in the apoplast, this study contributes to a deeper understanding of the events during peach softening and after HT with a focus on this key compartment.